Reversible Oxidative Modifications in Myoglobin and Functional Implications - Mark H. Mannino; Rishi S. Patel; Amanda M. Eccardt; Blythe E. Janowiak; David C. Wood; Fahu He; Jonathan S. Fisher (MDPI AG, 2020)
Myoglobin (Mb), an oxygen-binding heme protein highly expressed in heart and skeletal muscle, has been shown to undergo oxidative modifications on both an inter- and intramolecular level when exposed to hydrogen peroxide (H2O2) in vitro. Here, we show that exposure to H2O2 increases the peroxidase activity of Mb. Reaction of Mb with H2O2 causes covalent binding of heme to the Mb protein (Mb-X), corresponding to an increase in peroxidase activity when ascorbic acid is the reducing co-substrate. Treatment of H2O2-reacted Mb with ascorbic acid reverses the Mb-X crosslink. Reaction with H2O2 causes Mb to form dimers, trimers, and larger molecular weight Mb aggregates, and treatment with ascorbic acid regenerates Mb monomers. Reaction of Mb with H2O2 causes formation of dityrosine crosslinks, though the labile nature of the crosslinks broken by treatment with ascorbic acid suggests that the reversible aggregation of Mb is mediated by crosslinks other than dityrosine. Disappearance of a peptide containing a tryptophan residue when Mb is treated with H2O2 and the peptide's reappearance after subsequent treatment with ascorbic acid suggest that tryptophan side chains might participate in the labile crosslinking. Taken together, these data suggest that while exposure to H2O2 causes Mb-X formation, increases Mb peroxidase activity, and causes Mb aggregation, these oxidative modifications are reversible by treatment with ascorbic acid. A caveat is that future studies should demonstrate that these and other in vitro findings regarding properties of Mb have relevance in the intracellular milieu, especially in regard to actual concentrations of metMb, H2O2, and ascorbate that would be found in vivo.